2017
DOI: 10.1109/tmc.2016.2591528
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of Frame Slotted Aloha Protocol

Abstract: Frame Slotted Aloha (FSA) protocol has been widely applied in Radio Frequency Identification (RFID) systems as the de facto standard in tag identification. However, very limited work has been done on the stability of FSA despite its fundamental importance both on the theoretical characterisation of FSA performance and its effective operation in practical systems. In order to bridge this gap, we devote this paper to investigating the stability properties of FSA by focusing on two physical layer models of practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…FSA systems have VOLUME 7, 2019 stability issues when the tags contending and the number of slots in the FSA interrogation frame is unbalanced, causing either many collisions or many empty slots and thus inefficiency in the interrogation process. Some examples of works on this topic are [33]- [36] (see also references therein). Their goal is proposing and analyzing variations of the tag anti-collision protocol to achieve a constant (stable) performance.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…FSA systems have VOLUME 7, 2019 stability issues when the tags contending and the number of slots in the FSA interrogation frame is unbalanced, causing either many collisions or many empty slots and thus inefficiency in the interrogation process. Some examples of works on this topic are [33]- [36] (see also references therein). Their goal is proposing and analyzing variations of the tag anti-collision protocol to achieve a constant (stable) performance.…”
Section: Related Workmentioning
confidence: 99%
“…Their goal is proposing and analyzing variations of the tag anti-collision protocol to achieve a constant (stable) performance. For example, Yu and Chen [33] discussed multiple and single packet reception p-persistent FSA protocols, Qian et al [34] proposed a scheme named ASAP to adaptively split the tag set into multiple subsets, estimating the cardinalities during the splitting to adapt the frame length. Jia et al [35] introduced a new anti-collision protocol named collision tree protocol (CT) and showed that it achieves constant time delay and power consumption for one-tag identification.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…It is mainly categorized into two types: probabilistic anti-collision protocols based on Aloha 10,11 and deterministic anti-collision protocols based on trees. 12 The former includes slotted Aloha, 13 frame-slotted Aloha (FSA), 14 dynamic frameslotted Aloha (DFSA), 15 and so on. The latter contains binary search (BS) protocol, 16 query tree (QT) protocol, 17 collision tree (CT) protocol, 18 and so on.…”
Section: Introductionmentioning
confidence: 99%